Respuesta :

[tex]\underbrace{35x^4y+14x^5y-2y^3-4xy^3}_M\,\mathrm dx+\underbrace{7x^5-6xy^2}_N\,\mathrm dy=0[/tex]

[tex]M_y=35x^4+14x^5-6y^2-12xy^2[/tex]
[tex]N_x=35x^4-6y^2[/tex]

[tex]\dfrac{N_x-M_y}N=\dfrac{-14x^5+12xy^2}{7x^5-6xy^2}=-2[/tex]

This suggests an integrating factor depending on [tex]x[/tex] only is possible, and given by

[tex]\mu(x)=\exp\left(-\displaystyle\int\frac{N_x-M_y}N\,\mathrm dx\right)=e^{2x}[/tex]

Distributing across the ODE, we end up with

[tex]\underbrace{(35x^4y+14x^5y-2y^3-4xy^3)e^{2x}}_{M^*}\,\mathrm dx+\underbrace{(7x^5-6xy^2)e^{2x}}_{N^*}\,\mathrm dy=0[/tex]

The equation is now exact, with

[tex]{M^*}_y={N^*}_x=(35x^4+14x^5-6y^2-12xy^2)e^{2x}[/tex]

Now we find the solution:

[tex]F_x=M^*[/tex]
[tex]F=\displaystyle\int(35x^4+14x^5-2y^3-4xy^3)e^{2x}\,\mathrm dx[/tex]
[tex]F=(7x^5y-2xy^3)e^{2x}+f(y)[/tex]

[tex]F_y=N^*[/tex]
[tex](7x^5-6xy^2)e^{2x}+f'(y)=(7x^5-6xy^2)e^{2x}[/tex]
[tex]f'(y)=0[/tex]
[tex]\implies f(y)=C[/tex]

The general solution is then

[tex]F(x,y)=(7x^5y-2xy^3)e^{2x}=C[/tex]
ACCESS MORE